The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/tea.21334
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and motivational outcomes of lab work in the secondary intermediate track: The contribution of a science center outreach lab

Abstract: Students’ interest in science declines in secondary school. Therefore, motivating students to become competent and engaged in science topics that are relevant for their everyday lives is an important goal, so they can be better citizens and decision makers with socioscientific issues (e.g., climate change and waste disposal). The present study contributes to research on activity emotions (state) and motivational outcomes (situational interest and situational competence) in science education. The study compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 108 publications
3
62
0
Order By: Relevance
“…and "Did you enjoy what you were doing?" These items have been used extensively in prior research (see Hektner, Schmidt, & Csikszentmihalyi, 2007 for a review), and the composite measures are consistent with prior research efforts to measure behavioral, cognitive, and affective engagement using a person-oriented approach (Conner & Pope, 2013).…”
Section: Methodsmentioning
confidence: 66%
“…and "Did you enjoy what you were doing?" These items have been used extensively in prior research (see Hektner, Schmidt, & Csikszentmihalyi, 2007 for a review), and the composite measures are consistent with prior research efforts to measure behavioral, cognitive, and affective engagement using a person-oriented approach (Conner & Pope, 2013).…”
Section: Methodsmentioning
confidence: 66%
“…Furthermore, there was a difference with respect to gender, with the female adolescents benefitting: they reported more favorable motivational outcomes in the practical part (Itzek-Greulich & Vollmer, 2017). However, other studies revealed no gender difference.…”
Section: Personality Traitsmentioning
confidence: 89%
“…The gender has an influence on the topics of interest: Male adolescents are more interested in research, dangerous applications in science, physics, and technology, whereas female adolescents are more interested in natural phenomena overall and topics that deal with the body (Holstermann & Bögeholz, 2007). There are also gender effects regarding experiments, with female adolescents reporting more enjoyment, situational interest, competence, and less negative emotions than male adolescents (Itzek-Greulich & Vollmer, 2017). Furthermore, the perception of experiments is gender specific.…”
Section: Personality Traitsmentioning
confidence: 98%
“…However, in the literature, many suggestions for better science teaching can be found that clearly involve social activities and thus could activate empathizing skills, like science center outreach labs (Itzek‐Greulich & Vollmer, ), museum visits (Martin, Durksen, Williamson, Kiss, & Ginns, ), collaborative projects (Bryan et al, ), integrating students’ existing interests (Hagay & Baram‐Tsabari, ), science story telling (Polman & Hope, ), fostering autonomy, relatedness and belonging (Andersen & Nielsen, ), preventing feelings of disgust and rejection (Randler, Hummel, & Wüst‐Ackermann, ), knowledgeable, inspiring, enthusiastic, and caring teachers (Bryan et al, ; Keller, Neumann, & Fischer, ) that take students’ emotions into account (King, Ritchie, Sandhu, Henderson & Boland, ), and family and friends that encourage them to study science (Mujtaba & Reiss, ; Simpkins, Price, & Garcia, ).…”
Section: Discussionmentioning
confidence: 99%